The Intentional Interprofessional Education Model: A Conceptual Framework to Achieve an Interprofessional, Team-Based Approach in a Student Run Clinic - Jessica Nelson; Emma Hart; Eliana Otero-Bell; Heidi Rogers; Lindsay Fox; Anthony Fleg (Journal of Student-Run Clinics, 2023)
We introduce the conceptual framework of the Intentional Interprofessional Education (Intentional IPE) Model based on the understanding that it takes mindfulness and intentionality for interprofessional teams to build relationships and work together effectively in a structured manner at a Student-Run Clinic (SRC). This Intentional IPE Model developed organically through experiences and conversations over several years among patients, students, and faculty at a SRC in Albuquerque, New Mexico, serving men experiencing homelessness. Teamwork is at the heart of the Intentional IPE Model, and it is also centered on the following values: curiosity, reflective listening, role exploration, vulnerability, respect, mentorship, and patient partnership. For students and faculty to engage in deep and productive interprofessional learning, professional health philosophies, priorities, and roles must be laid out, and curiosity should be encouraged. Our reflective paper emphasizes the ways the Intentional IPE Model can enhance student-faculty-patient experiences in SRC settings